2017
DOI: 10.1212/wnl.0000000000004611
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clinical features of neuromyelitis optica spectrum disorders in northern Japan

Abstract: Our results showed that the prevalence of NMOSD in the Japanese population is similar to that in Caucasians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
57
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 21 publications
10
57
1
Order By: Relevance
“…A trend toward fewer relapses from February to April compared to a peak from November to January is similar to the pattern seen in MS both in the Northern and Southern Hemisphere (9,10). This finding is somewhat surprising considering the absence of a latitudinal gradient seen in two national studies of NMOSD prevalence (4,20). This suggests that relative vitamin D deficiency or decreased ultraviolet B radiation exposure are not significant factors in the risk of developing NMOSD but may be factors influencing the likelihood of relapses.…”
Section: Discussionsupporting
confidence: 50%
“…A trend toward fewer relapses from February to April compared to a peak from November to January is similar to the pattern seen in MS both in the Northern and Southern Hemisphere (9,10). This finding is somewhat surprising considering the absence of a latitudinal gradient seen in two national studies of NMOSD prevalence (4,20). This suggests that relative vitamin D deficiency or decreased ultraviolet B radiation exposure are not significant factors in the risk of developing NMOSD but may be factors influencing the likelihood of relapses.…”
Section: Discussionsupporting
confidence: 50%
“…A previous Japanese nationwide survey revealed that the estimated crude prevalence of MS in Japan is 7.7/100 000, while another recent study reported a crude NMOSD prevalence of 4.1/100 000 in a local area of Hokkaido located in Northern Japan 3. In their  JNNP  paper, Miyamoto and colleagues first showed the results of a nationwide survey conducted in Japan based on a well-designed epidemiological methodology and the 2006 Wingerchuk criteria for NMO; the estimated prevalence was 1.64 per 100 000 for NMO and 3.42 for NMOSD 4.…”
Section: Genetic and Environmental Risk Factors Are Distinct In Nmosdmentioning
confidence: 97%
“…Some differences have been reported in the prevalence of cognitive impairment among patients with NMOSD and MS. For example, although patients with NMOSD had core deficits in attention and information processing speed, patients with MS had more widespread cognitive impairment. 75 Therefore, neurologists need to consider which batteries are adequate to evaluate cognitive functions in NMOSD versus MS. Fujimori et al reported that the BRB-N misevaluated multiple cognitive functions in patients with NMOSD aged >55 years.…”
Section: Cognition In Nmosdmentioning
confidence: 99%
“…74 Furthermore, the average age at the onset of NMOSD is older than that of MS; for instance, an age of onset >60 years is not rare in NMOSD. 75 Therefore, neurologists need to consider which batteries are adequate to evaluate cognitive functions in NMOSD versus MS.…”
Section: Cognition In Nmosdmentioning
confidence: 99%